Pengaruh Harga dan Promosi terhadap Keputusan Pembelian pada Toko Alfamart Cemara 2 Karawaci Tangerang Banten - Jastini, Jastini; Nurul Faroh, Wahyu (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research aims to determine the effect of price and promotion on purchasing decisions at the Alfamart Cemara2 Karawaci Store. This research uses quantitative methods. The data source for this research is primary data from a sample of Alfamart Cemara2 Karawaci consumers. Data collection was carried out using a Slovin sample with a population of 91 respondents. The results of this research show that price has a significant positive influence on purchasing decisions. Promotion has a significant positive influence on purchasing decisions. Price and promotion have a significant positive influence simultaneously on purchasing decisions by showing that the Fcount value is 461.132 > Ftable 3.100 or the sig value is 0.000b < 0.05. So H0 is rejected and H3 is accepted.